PERCERAIAN USIA 3 TAHUN PERKAWINAN DARI PASANGAN MUDA - Siah Khosyi’ah; Gozwan M. Jundan (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
Law No. 1 of 1974 concerning marriage explains that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy family (household) based on the divinity of the Almighty. However, it was found several decisions of the Garut Religious Court which showed the age of marriage which lasted a short period of time. This study aims to determine the factors causing divorce at the age of 3 years of marriage from a young couple in the Garut Religious Court, to find out the legal reasons for judges for divorce at the age of 3 years of marriage from a young couple in the Religious Court of Garut and the judge's view of the granting of a 3 year marriage divorce decision. from a young couple in the Garut Religious Court. The results showed that the factors causing divorce at the age of 3 years of marriage can be classified into 3 main causes, namely: disputes and quarrels, lack of responsibility from the spouse and interference from outside parties. The legal reasons for judges who are sufficient to meet the reasons for divorce based on the law of several examples of decisions include: based on the information submitted before the trial the judge found the fact that between couples often quarrels and disputes occur and are not responsible for obligations in fulfilling the needs of living , as well as the parties split up residence.Undang-undang Nomor 1 tahun 1974 tentang perkawinan menjelaskan bahwa perkawinan ialah ikatan lahir bathin antara seorang pria dan seorang wanita sebagai suami istri dengan tujuan membentuk keluarga (rumah tangga) yang bahagia kekal berdasakan ketuhanan Yang Maha Esa. Namun ditemukan beberapa putusan Pengadilan Agama Garut yang menunjukan adanya usia perkawinan yang berlangsung dalam kurun waktu yang singkat. Penelitian ini bertujuan untuk mengetahui faktor penyebab perceraian usia 3 tahun perkawinan dari pasangan muda di Pengadilan Agama Garut, untuk mengetahui alasan hukum hakim atas perkara perceraian usia 3 tahun perkawinan dari pasangan muda di Pengadilan Agama Garut dan pandangan hakim terhadap dikabulkannya putusan perceraian usia 3 tahun perkawinan dari pasangan muda di Pengadilan Agama Garut. Hasil penelitian menunjukan bahwa faktor penyebab terjadinya perceraian usia 3 tahun perkawinan dapat digolongkan menjadi 3 penyebab utama, yaitu: perselisihan dan pertengkaran, tidak adanya tanggung jawab dari pasangan dan gangguan dari pihak luar. Adapun alasan hukum hakim yang cukup memenuhi alasan perceraian berdasarkan undang-undang dari beberapa contoh putusan antara lain: berdasarkan keterangan yang diajukan di depan muka persidangan hakim menemukan fakta bahwa diantara para pasangan sering terjadi pertengkaran dan perselisihan dan tidak bertanggung jawab dalam kewajiban dalam memenuhi kebutuhan nafkah, serta para pihak berpisah tempat tinggal.